PELATIHAN PEMBUATAN KEJU MOZARELLA DAN PUDING UNTUK MENINGKATKAN HARGA JUAL SUSU - Herawati, Erna; Maharani, Dian; Hikmah, Nurul (Universitas Djuanda, 2023)
This research was conducted through post-dairy processing of cow's milk into mozzarella cheese and pudding. The subjects of this study were residents of Ngenep Village, Karangploso District, Malang Regency, especially PKK women. With this training, it is hoped that the milk’s price will double, so that the public earning will increase. The method used in this research is Asset Based Community Development (ABCD) method. Keywords: training, mozzarella, pudding, ABCD.